CONVERSATION AND COMMUNITY BUILDING IN PRIDE AND PREJUDICE - Sisi Han (Universitas Islam Sumatera Utara (UISU), 2018)
The thematic research on Jane Austen’s novels has been widely carried out, including marriage, gender, morality, politics, etc. The conception of community is also an important theme for her novels are set in a period when the notion of community is conceived and reinforced in the West. It is a transitional age that witnesses the change from the 18th century when the feudal aristocracy controls the agricultural economy to the 19th century which is dominated by the middle class as a result of the Industrial Revolution. However, the theme of community has not got enough critical attention and its research is sparse. Thus, this dissertation seeks to explore Austen’s contribution to the conception of community in Pride and Prejudice. Austen’s imagination of community is effectively displayed in Pride and Prejudice and conversation serves as a key approach. The Community is built at two levels, namely, familial level and social level. By means of conversation, a family bond based on mutual affirmation, which is the core of community building, is forged; and a community of spirit, the highest form of community, is established among social interactions outside families in two social spaces– Meryton and Pemburley. A stereoscopic vision of a community built by conversation emerges when the three levels are closely intertwined.